The Spectrum of Histopathological Lesions in Children Presenting with Steroid-Resistant Nephrotic Syndrome at a Single Center in Pakistan. (2nd May 2012) - Mubarak, Muhammed; Kazi, Javed I.; Shakeel, Shaheera; Lanewala, Ali; Hashmi, Seema
Abstract : Steroid-resistant nephrotic syndrome (SRNS) is a common problem in pediatric nephrology practice. There is currently little information in the literature on the spectrum of histopathologic lesions in children presenting with SRNS in Pakistan. This study was designed to determine the histopathologic lesions in children presenting with SRNS at our center. The study was conducted at the Histopathology Department, Sindh Institute of Urology and Transplantation (SIUT) from January 2009 to August 2011. All children (≤16 years) presenting with SRNS, in whom renal biopsies were performed, were included. Their demographic, clinical, laboratory, and histopathological data were retrieved from files and original renal biopsy forms. The results were analyzed by SPSS version 10.0. A total of 147 children were included. Of these, 91 (61.9%) were males and 56 (38.1%) females, with male-to-female ratio of 1.6 : 1. The mean age was 7.03 ± 4.0 years (range: 6 months–16 years). The histopathological lesions seen on renal biopsies comprised of focal segmental glomerulosclerosis (FSGS) (38.5%), followed by minimal change disease (MCD) (23.2%), IgM nephropathy (IgMN) (13.6%), idiopathic mesangial proliferative GN (10.2%), membranous GN (8.2%), and mesangiocapillary GN (4.8%). Our results indicate that FSGS is the predominant lesion in children with SRNS, followed by MCD and IgMN.